2018
DOI: 10.1155/2018/2137091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Coloring Procedures on the Aging Behavior of Dental Monolithic Zirconia

Abstract: Objective.is study aimed to investigate the effect of different coloring procedures on the aging behavior of dental monolithic zirconia. Methods. Two types of translucent zirconia (SuperfectZir HTS, Aidite; Katana HT, Kuraray) were tested. Bar-shaped specimens with dimensions of 22 × 4 × 2 mm were prepared from uncolored and precolored blocks. Before being sintered, specimens made from uncolored blocks were colored by dipping them into a coloring liquid, whereas the precolored specimens were not treated. e spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The study's findings demonstrated that after aging, A2 liquid-shaded zirconia's flexural strength was lower than that of A2 pre-shaded zirconia, but this difference was statistically non-nsignificant. This is in agreement with Agingu et al (2018) (65) investigated the impact of various coloring techniques on the aging behavior of monolithic zirconia and came to the non-significant conclusion that aging and coloring techniques decreased flexural strength.…”
Section: Discussionsupporting
confidence: 89%
“…The study's findings demonstrated that after aging, A2 liquid-shaded zirconia's flexural strength was lower than that of A2 pre-shaded zirconia, but this difference was statistically non-nsignificant. This is in agreement with Agingu et al (2018) (65) investigated the impact of various coloring techniques on the aging behavior of monolithic zirconia and came to the non-significant conclusion that aging and coloring techniques decreased flexural strength.…”
Section: Discussionsupporting
confidence: 89%
“…At ambient pressure, zirconia can exhibit 3 allotropic crystal phase structures: a monoclinic phase ( m ) from room temperature to 1170°C, a tetragonal phase ( t ) from 1170°C to 2370°C, and a cubic phase ( c ) above 2370°C to its melting point at 2715°C and boiling point of 4300°C [ 4 , 5 ]. To stabilize the t and c phases of zirconia at room temperature, the addition of different amount of stabilizing oxides, such as yttria (Y 2 O 3 ), to pure zirconia crystals is essential and well studied [ 2 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported no significant reduction in the flexural strength of Y-TZP material after aging. 30 This is possibly related to the inherited property of zirconia that is capable of exhibiting low-temperature degradation (LTD) properties. Once the Y-TZP is exposed to the aging process, which was in a humid environment for a long period, the water molecules are capable of penetration into the zirconia structure.…”
Section: Discussionmentioning
confidence: 99%